PENERAPAN SOFT SYSTEMS METHODOLOGY (SSM) DALAM PENYELESAIAN MASALAH KOMPLEKS DI LEMBAGA PENDIDIKAN - Susanto, Teguh Trianung Djoko; Lusiana, Lufita; Trimiltin, Ricky; Runiasih, Mawar (STKIP Pesisir Selatan, 2025)
Educational institutions are often faced with complex, unstructured problems, involving many stakeholders with different perspectives and interests. Such problems cannot be solved with a technical approach alone, but require an adaptive and participatory systemic approach. This study aims to examine the application of Soft Systems Methodology (SSM) as a qualitative approach to solving complex problems in the educational environment. The study was conducted through a systematic literature review of ten scientific articles published between 2020 and 2025, obtained from the Scopus, Google Scholar, and Garuda databases. The search process used the keywords